Safety of multi-access site venous closure following catheter ablation of atrial fibrillation and flutter - Gupta, Sanjaya; Kolluri, Raghu; Simoes, Tiessa; Pingle, Sandeep C.; Nie, Hong; Lloyd, Michael S.; Steinhaus, Daniel; Westerman, Stacy B.; Shah, Anand; Kline, Jessica; Kiani, Soroosh (Journal of interventional cardiac electrophysiology, 2024)
Background Following catheter ablation, vascular access management involves potential complications and prolonged recovery. Recently, suture-mediated closure (SMC) devices were approved for venous access procedures. The objective of this study is to evaluate the safety of a commercially available SMC for multiple access site venous closure by duplex ultrasound (DUS) in asymptomatic subjects with non-visible complications. Methods Thirty-six subjects (63 ± 10.7 years old, 12 female) were enrolled. Following catheter ablation for atrial fibrillation, all subjects had SMC of every venous access site. Subjects underwent DUS of femoral veins and arteries. DUS was performed at discharge, and again at 30 days. Subjects were evaluated for clinically apparent vascular complications. Results Mean procedure duration was 138.6 min, and the time to hemostasis was 3.1 min/access site and 9.5 min/subject. Median time to ambulation was 193.5 min, and median time to discharge was 5.95 h, with discharge as early as 2.4 h. A median of 2 sheaths/vein and a median of 2 SMC devices/vein were used. There were no major complications and a 16.7% (6/36) minor complication rate at discharge. All complications resolved at 30 days. The complication rate was not higher in patients with 2 SMC per access site as compared to the patients who just received 1 SMC per access site. Conclusions This study demonstrates the safety of multi-access closure using SMC, following catheter ablation procedures, for closure of sites that use sheath sizes from ≤ 8F to ≥ 15F and for those that use 2 or more SMCs per access site. Graphical abstract